The effects of eccentric training on hamstring muscle architecture : a systematic review - Emirzeoğlu, Murat (Array, 2021)
The architectural features of the hamstring muscle group are important to prevent injury or to reduce the risk of re-injury. Besides, eccentric training is often used in the rehabilitation of hamstring injuries. The aim of this systematic review was to examine the changes created by eccentric training on hamstring muscle architecture and to determine the minimal values of training duration and intensity for requiring functional changes. The research was conducted on the PubMed, Scopus, Web of Science, COCHRANE, CINAHL, and Pedro databases. Full-text studies examining the effect of eccentric training on at least one parameter of the hamstring muscle architecture were included in the review. Studies on cadavers and animals and studies involving different types of training combined with eccentric training were excluded. Twelve of the 7954 studies met the set criteria. According to the results, eccentric training undoubtedly increases fiber length. However, the pennation angle tends to decrease. On the other hand, muscle thickness and cross-sectional area tends to increase depending on the eccentric training. Although the frequency, number of sets and number of repetitions in sets were similar in the examined studies, muscle architecture changes were different. We think that eccentric training duration and the number of repetitions in total or per training session seem to have an impact on muscle architecture. In order to determine the minimal eccentric training program that can create these changes, quality research is needed to examine the duration, intensity and methods of eccentric training.